Mereduksi Superioritas dan Mengamalkan Sila Kemanusian yang Adil dan Beradab dalam Perspektif Kristiani - Yonatan Alex Arifianto (Sekolah Tinggi Teologi Paulus Medan, Sumatra Utara, 2021)
The diversity of the Indonesian population on the one hand is the strength of the Indonesian nation, but it can also be a trigger for the disintegration of fellow nation's children. The number of SARA conflicts that occurred after the reformation gave rise to superiority in various levels of society to the superiority of religion. Through this paper, the writer describes reducing superiority and practising just and civilized human precepts. Using descriptive qualitative research methods, it can be concluded that in order to reduce superiority and also in practising the precepts and norms contained therein, what needs to be done as follows: First, every child of the nation must be able to eliminate the sense of superiority from all sides towards respect for others by reducing the wrong paradigm of the nature of humanity. Second, continue to strengthen and continue to practice unity and integrity as the basis of the nation and state. Third, believers can see the human side from a Christian perspective which can be a guide in actualizing the Christian faith in upholding human values. Abstrak Keberagaman penduduk Indonesia di satu sisi merupakan kekuatan bangsa Indonesia, namun juga dapat menjadi pemicu disintegrasi sesama anak bangsa. Banyaknya konflik SARA yang terjadi setelah reformasi, menimbulkan superioritas diberbagai lapisan masyarakat sampai kepada superioritas agama. Melalui tulisan ini penulis mendeskripsikan tentang mereduksi superioritas seba-gai pengamalan sila “Kemanusian yang adil dan beradab”. Dengan menggunakan metode penelitian kualitatif deskritif, dapat disimpulkan bahwa untuk mereduksi superioritas dalam mengamalkan sila dan norma yang terkandung di dalamnya maka yang perlu dilakukan sebagai berikut: Pertama, setiap anak bangsa harus dapat menghilangkan rasa superior atas sikap menghargai sesama dengan mere-duksi paradigma hakikat kemanusiaan yang salah. Kedua, tetap memperkokoh dan terus meng-amalkan persatuan dan kesatuan sebagai dasar hidup berbangsa dan bernegara. Ketiga, orang percaya dapat melihat sisi kemanusiaan dalam perspektif Kristiani yang dapat menjadi tuntunan untuk mengaktualisasi iman Kristen dalam menjunjung tinggi nilai kemanusiaan.